2016
DOI: 10.1039/c6ra11233a
|View full text |Cite
|
Sign up to set email alerts
|

Concise approach to pyrrolizino[1,2-b]indoles from indole-derived donor–acceptor cyclopropanes

Abstract: A direct approach to previously unexplored pyrrolizidino[1,2-b]indole system from indole-derived donor–acceptor cyclopropanes based on a sequence of three synthetic steps was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Next, we applied the reaction conditions optimized for the one ‐ pot transformation of 1 a to 3 a (Table 3, entry 9) for the synthesis of a series of 4‐azidobutyrates 3 (Scheme 4). Although the yields of the designed transformation were moderate and lower than those described earlier, [13,14d,f] these conditions granted a tremendous reaction rate increase. Thus, treating D‐A cyclopropane 1 a either at 100 °C for 7 h or at 120 °C for 2 h independently furnished the desired azide 3 a , while the conventional method required around 20 h on average.…”
Section: Resultsmentioning
confidence: 74%
“…Next, we applied the reaction conditions optimized for the one ‐ pot transformation of 1 a to 3 a (Table 3, entry 9) for the synthesis of a series of 4‐azidobutyrates 3 (Scheme 4). Although the yields of the designed transformation were moderate and lower than those described earlier, [13,14d,f] these conditions granted a tremendous reaction rate increase. Thus, treating D‐A cyclopropane 1 a either at 100 °C for 7 h or at 120 °C for 2 h independently furnished the desired azide 3 a , while the conventional method required around 20 h on average.…”
Section: Resultsmentioning
confidence: 74%
“…Synthesis of intermediate cyclopropanes 2 was performed through sequential Knoevenagel and Corey-Chaykovsky reactions according to the literature procedures. , Cyclopropanes 2a – i were obtained in good yields as diastereomeric mixtures. In order to carry out transformation of cyclopropanes 2 into azides 3 , we have modified the reaction conditions, previously reported by us for the nucleophilic ring opening of donor–acceptor cyclopropanes with the azide ion . To achieve complete 2 -to- 3 conversion, this process was thermally activated in a microwave reactor.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported original access to pyrrolidine derivatives via a cascade of Staudinger/ aza -Wittig/Mannich reactions of carbonyl compounds with readily available organic azides, wherein the 1,3-relationship between the azido group and an activated CH-fragment provided desired reactivity (Scheme B). In this context, our further efforts were directed toward the development of a new approach to spiro­[pyrrolidine-3,3′-oxindoles] based on our original strategy for pyrrolidine assembly.…”
Section: Introductionmentioning
confidence: 99%
“…[165][166][167] The method for the synthesis of 213 relied upon nucleophilic ring opening of DA cyclopropanes 212 activated with aryl-, hetaryl-, and alkenyl-substituents as the EDG (R) and ester, acyl, nitro, and cyano groups as EWG with the azide ion (Scheme 120). 165 The experimental data showed that the reaction proceeded via an S N 2-like mechanism with reversal of configuration at the electrophilic center of cyclopropane 212.…”
Section: Scheme 119mentioning
confidence: 99%